2012
DOI: 10.1080/10503307.2012.662608
|View full text |Cite
|
Sign up to set email alerts
|

Is treatment in a day hospital step-down program superior to outpatient individual psychotherapy for patients with personality disorders? 36 months follow-up of a randomized clinical trial comparing different treatment modalities

Abstract: Despite increasing interest in the development of effective treatments for patients with PDs, there is still no consensus about the optimal treatment setting for this group of patients. This study reports the 36 months follow-up of the Ullevål Personality Project (UPP) (n=113), a randomized clinical trial comparing two treatment modalities for patients with PDs: an intensive long-term step-down treatment program, consisting of short-term day hospital treatment followed by combined group and individual psychoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
4
26
0
3
Order By: Relevance
“…However, the transition from day-hospital to outpatient treatment in the CP that included a change of therapists may have represented a disruption of the therapeutic process, causing delayed improvement for patients in the CP (Hummelen, Wilberg, & Karterud, 2007). This possibility is supported by the higher level of psychosocial functioning in the OIP condition at three-year follow-up (Gullestad et al, 2012). Further, publications by Bateman and Fonagy (2009) and Jørgensen et al (2013) support the effectiveness of intensive combination therapy in an outpatient setting.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…However, the transition from day-hospital to outpatient treatment in the CP that included a change of therapists may have represented a disruption of the therapeutic process, causing delayed improvement for patients in the CP (Hummelen, Wilberg, & Karterud, 2007). This possibility is supported by the higher level of psychosocial functioning in the OIP condition at three-year follow-up (Gullestad et al, 2012). Further, publications by Bateman and Fonagy (2009) and Jørgensen et al (2013) support the effectiveness of intensive combination therapy in an outpatient setting.…”
Section: Discussionsupporting
confidence: 48%
“…Originally, UPP was a study including a mixed PD sample, and we have previously reported results for the total sample from the follow-up investigations at 8 months, 18 months, 3 years, and 6 years after the initial random assignment (Antonsen et al, 2014;Arnevik et al, 2009Arnevik et al, , 2010Gullestad et al, 2012). At six-year follow-up, differences between the two treatment conditions were below levels of significance, although different trends were observable (Antonsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrawal, Gunderson, Holmes, & Lyons-Ruth, 2004 for a review) as well as between BPD and RF dysfunctions (e.g., Fonagy et al, 1996;Gullestad et al, 2012;Harari, Shamay-Tsoory, Ravid, & Levkovitz, 2010;Preissler, Dziobek, Ritter, Heekeren, & Roepke, 2010). These studies underline the relevance of adult attachment patterns sustained by negative self internal working model while other findings have also highlighted the importance of negative internal working model of others.…”
mentioning
confidence: 91%
“…These studies underline the relevance of adult attachment patterns sustained by negative self internal working model while other findings have also highlighted the importance of negative internal working model of others. As a whole, these results lead many to consider that BPD patients may fluctuate in the valence of internal working models of self and others (for a review see Agrawal et al, 2004) In terms of mentalization, BPD patients are typically described as struggling to effortfully engage cognitive resources when attributing mental states (e.g., Fonagy et al, 1996;Gullestad et al, 2012;Harari et al, 2010;Preissler et al, 2010). This feature in their mentalization profile may bias the interpretation of mental states that motivate self and other"s action, towards automatic and affectively-based reasoning, which strongly reduces their emotion regulation success (Fonagy & Luyten, 2009).…”
mentioning
confidence: 99%